Defying syntactic preservation in Alzheimer's disease: what type of impairment predicts syntactic change in dementia (if it does) and why? - Ivanova, Olga; Martínez-Nicolás, Israel; García-Piñuela, Elena; Meilán, Juan José G. (Frontiers in Language Sciences, 2023)
Introduction Many studies on syntax in dementia suggest that, despite syntactic simplification, speakers with Alzheimer's disease (AD) retain their basic grammatical abilities, being mainly affected in their comprehension and production of complex syntax. Moreover, there is no single position on the origin of syntactic decline in AD, which, according to some authors, can be linked to a lexical-semantic deficit or, according to others, to either cognitive or autonomous dysfunction. Methods In this study, we apply the model of syntactic maturity to the analysis of oral speech production elicited by the Cookie-Theft description task. We assess a sample of 60 older adults (21 HC, 19 MCI, and 20 AD) through three indexes of syntactic maturity, measuring the proportion of sentences and clauses in discourse, their mean length, and the rate of their complexity. Results Our results show two important tendencies in AD: the preservation of general syntactic ability, as measured by the basic syntactic organization of speech, and the disturbance of the indexes of syntactic complexity, as measured by the overall length of utterances and their indexes of complexity. Discussion Although speakers with AD maintain the ability to construct grammatically acceptable sentences and produce a similar number of utterances to healthy aging speakers and speakers with MCI, the syntactic complexity of their discourse significantly changes. Importantly, such significant changes are already present at the MCI stage and are not conditioned by the lexical-semantic deficit itself. Our results may be particularly relevant to improving the detection of cognitive impairment and to theoretically discussing the relationships between language levels in aging speakers.